Prognostic value of positive histological margins in patients with pancreatic head ductal adenocarcinoma and lymph node involvement: an international multicentric study. Issue 3 (March 2021) - Joliat, Gaëtan-Romain; Allemann, Pierre; Labgaa, Ismail; Sulzer, Jesse; Vrochides, Dionisios; Zerbi, Alessandro; Nappo, Gennaro; Perinel, Julie; Adham, Mustapha; Nentwich, Michael F.; Izbicki, Jakob R.; Demartines, Nicolas; et al.
Abstract: Background: Resection margin status and lymph node (LN) involvement are known prognostic factors for patients who undergo pancreatoduodenectomy for pancreatic ductal adenocarcinoma (PDAC). This study aimed to compare overall survival (OS) and disease-free survival (DFS) by resection margin status in patients with PDAC and LN involvement. Methods: A retrospective international multicentric study was performed including four Western centers. Multivariable Cox analysis was performed to identify prognostic factors of OS and DFS. Median OS and DFS were calculated using Kaplan–Meier curves and compared using log-rank tests. Results: A cohort of 814 PDAC patients with pancreatoduodenectomy were analyzed. A total of 651 patients had LN involvement (80%). On multivariable analysis R1 resection was not an independent factor of worse OS and DFS in patients with LN involvement (HR 1.1, p = 0.565; HR 1.2, p = 0.174). Only tumor size, grade, and adjuvant chemotherapy were associated with OS and DFS. Median OS and DFS were similar between patients with R0 and R1 resections (23 vs. 20 months, p = 0.196; 15 vs . 14 months, p = 0.080). Conclusion: Resection status was not identified as predictor of OS or DFS in PDAC patients with LN involvement. Extensive surgery to achieve R0 resection in such patients might not influence the disease course.